Increasing Activities of Daily Living Is as Easy as 1-2-3. (September 2016) - Best, Deanna; Osterkamp, Erin; Demmel, Kathleen; Kiniyalocts, Shivonne; Mock, Shawn; Mulligan, Kelly; Bell, Angela; Doughman, Crystal; Flemming, Miranda; Flesch, Laura; Hawkins, Deanna; Pate, Abigail; et al.
Background: Human flora are the most common cause of bacteremia in immunocompromised patients. Activities of daily living (ADL), including oral care and daily chlorhexidine gluconate bathing, can lower the risk of infection.Methods: To address ADL compliance in our pediatric oncology and bone marrow transplant patients, we adopted the ADL 1-2-3 initiative: daily chlorhexidine gluconate bath and linen change, at least 2 activities per day, and oral care 3 times per day. Using the Model for Improvement we created a standardized ADL process that involved all providers. Interventions included addressing ADL 1-2-3 compliance during rounds, establishing accountability in care delivery, an oral care order set and algorithm, daily text message reminders, and physician intervention with noncompliant and high-risk patients.Results: With our interventions, we increased our median compliance with the all-or-none ADL 1-2-3 initiative from 25% to 66% in 90 days. We have sustained our median compliance to 75% sixteen months after implementation. The greatest impact on compliance was seen with text message reminders to staff to complete and document the ADL 1-2-3 components, designated roles and responsibilities, and physician discussion with noncompliant and high-risk patients.Discussion: Oral care algorithm and order set, daily text message reminders, and physician intervention with noncompliant and high-risk patients has improved our compliance. Units where compliance with ADL participation is low can benefit from incorporating elements from this ADL 1-2-3 initiative.